Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1991
DOI: 10.1002/jcp.1041480105
|View full text |Cite
|
Sign up to set email alerts
|

Cell polarity regulates the release of secretory component, the epithelial receptor for polymeric immunoglobulins, from the surface of HT‐29 colon carcinoma cells

Abstract: The HT-29 human colon carcinoma cell line differentiates in glucose-free medium to an enterocytic phenotype. We previously isolated a series of HT-29 subclones selected for high levels of expression of secretory component (SC), the epithelial receptor for polymeric immunoglobulins. To develop a model system for studying effects of cell polarity on SC expression and release from the cell surface, the HT-29.74 subclone was induced to differentiate in glucose-free medium. Expression of SC was induced by glucose d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 39 publications
3
18
0
Order By: Relevance
“…Indeed, it has been shown that fucosylated oligosaccharides are associated with the inhibition of CFA 1 -and CFA2-mediated adhesion of ETEC strains26 and inhibit localised adhesion of EPEC strain^.^ Human milk contains many glycocompounds, some of which are rich in fucosylated oligosaccharides, such as Lf and free secretory component (fSC), which are found in abundance.l2' l6, 28-30 Th e secretory component (SC) mediates the transport of sIgA into external fluids on mucosal epithelial cells, and can be found in secretions both complexed with sIgA (bound SC) or as an uncomplexed 80-kDa glycoprotein called free SC. [31][32][33] This study investigated a possible role for glycoproteins from human milk in the inhibition of the adhesion (haemagglutination) induced by ETEC CFA1+ strains, assaying, step by step, every fraction obtained in the chromatographic fractionation of the milk.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been shown that fucosylated oligosaccharides are associated with the inhibition of CFA 1 -and CFA2-mediated adhesion of ETEC strains26 and inhibit localised adhesion of EPEC strain^.^ Human milk contains many glycocompounds, some of which are rich in fucosylated oligosaccharides, such as Lf and free secretory component (fSC), which are found in abundance.l2' l6, 28-30 Th e secretory component (SC) mediates the transport of sIgA into external fluids on mucosal epithelial cells, and can be found in secretions both complexed with sIgA (bound SC) or as an uncomplexed 80-kDa glycoprotein called free SC. [31][32][33] This study investigated a possible role for glycoproteins from human milk in the inhibition of the adhesion (haemagglutination) induced by ETEC CFA1+ strains, assaying, step by step, every fraction obtained in the chromatographic fractionation of the milk.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have stressed the influence of epithelial cell polarization on SC secretion [10,11]. CHINTALA-CHARUVU et al [11] extensively demonstrated that depolarization, induced by calcium deprivation, significantly decreased the total release of SC by HT-29.74 human colon carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…CHINTALA-CHARUVU et al [11] extensively demonstrated that depolarization, induced by calcium deprivation, significantly decreased the total release of SC by HT-29.74 human colon carcinoma cells. Like FIEDLER et al [10] we found that SC release by HBEC in primary culture on permeable filters was apically polarized.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations